2018
DOI: 10.11124/jbisrir-2016-003248
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fasting interventions for treatment of overweight and obesity in adults: a systematic review and meta-analysis

Abstract: Intermittent energy restriction may be an effective strategy for the treatment of overweight and obesity. Intermittent energy restriction was comparable to continuous energy restriction for short term weight loss in overweight and obese adults. Intermittent energy restriction was shown to be more effective than no treatment, however, this should be interpreted cautiously due to the small number of studies and future research is warranted to confirm the findings of this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
212
1
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(246 citation statements)
references
References 37 publications
14
212
1
19
Order By: Relevance
“…The most common IF protocols adopted by people in attempt to lose weight involve daily fasting for up to 16 hours; or fasting periods of up to 24 hours interspersed with normal feeding days [3,4]. Despite demonstrated weight loss [5][6][7], more studies are needed to evaluate whether alternate-day IF diets promote health benefits or could cause undesired effects in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…The most common IF protocols adopted by people in attempt to lose weight involve daily fasting for up to 16 hours; or fasting periods of up to 24 hours interspersed with normal feeding days [3,4]. Despite demonstrated weight loss [5][6][7], more studies are needed to evaluate whether alternate-day IF diets promote health benefits or could cause undesired effects in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent fasting appears to produce similar results to CER in terms of weight loss and the associated changes in body composition and risk factors for metabolic disease. Several reviews , including some systematic reviews with or without meta‐analysis, concur that intermittent fasting in adults with overweight or obesity produces losses in body weight, fat mass and fat‐free mass, as well as improvements in risk factors for cardio metabolic disease (such as circulating levels of insulin, glucose or lipids) that are equivalent – albeit not superior – to those induced by CER. One caveat with this conclusion is that most of the reviewed publications were not sufficiently powered to fully assess all of these outcomes, and most outcomes were measured at less than 6 months after commencement of the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Fasting has been suggested as a promising approach for health benefits in animal models and humans [2,25]. Intermittent fasting in obese people showed that reducing calorie intake one to six days per week over at least 12 weeks was effective for reducing body weight [26]. Especially, the 5:2 diet has become a popular intermittent fasting regimen and has a potential to be considered for medical interventions.…”
Section: Discussionmentioning
confidence: 99%